Cognitive Effects of Atypical Antipsychotic Medications in Patients with Alzheimer’s Disease: Outcomes from CATIE-AD - Vigen, Cheryl L.P. (2011)
OBJECTIVE: The impact of the atypical antipsychotics, olanzapine, quetiapine and risperidone on cognition in patients with Alzheimer’s disease is unclear. This report describes the effects of time and treatment on neuropsychological function during the Clinical Antipsychotic Trials of Intervention Effectiveness Alzheimer’s disease study (CATIE-AD). METHOD: CATIE-AD included 421 Alzheimer’s disease outpatients with psychosis or agitated/aggressive behavior, randomized to masked, flexible-dose olanzapine, quetiapine, risperidone or placebo. Based on clinician’s judgment, patients could discontinue originally assigned medication and be randomized to another medication. They were followed for 36 weeks. Cognitive assessments were obtained at baseline, 12 weeks, 24 weeks and 36 weeks. Outcomes were compared among 357 patients with baseline and at least one follow-up cognitive measure obtained while on their prescribed medication or placebo for at least 2 weeks before cognitive testing. RESULTS: Overall, patients showed steady, significant declines over time in most cognitive areas, including Mini-mental State Examination (2.4 points over 36 weeks) and Alzheimer’s Disease Assessment Scale-cog (4.4 points). Patients on antipsychotics declined more than patients on placebo on multiple cognitive measures, including the MMSE (p=0.004), BPRS cognitive subscale (p=0.05), and a cognitive summary score summarizing change on 18 cognitive tests (p=0.004). CONCLUSIONS: In CATIE-AD atypical antipsychotics were associated with worsening cognitive function at a magnitude consistent with one year’s deterioration compared with placebo. Further cognitive impairment is an additional risk of atypical antipsychotic treatment for Alzheimer’s disease patients that should be considered when considering treatment.